Comparison of femtosecond laser-assisted deep anterior lamellar keratoplasty and penetrating keratoplasty for keratoconus - Chen, Yueqin (BMC Ophthalmol, 2015)
BACKGROUND: To compare outcomes of femtosecond laser-assisted deep anterior lamellar keratoplasty (FSL-DALK) and penetrating keratoplasty (FSL-PK) for the treatment of keratoconus. METHODS: Twenty eight eyes underwent FSL-DALK (consisted of 12 eyes in the FSL-DALKa subgroup without baring the Descemet’s membrane and 16 eyes in the FSL-DALKb subgroup baring the Descemet’s membrane using big-bubble technique) were compared with 12 eyes that underwent FSL-PK for keratoconus. These patients underwent an ophthalmic examination preoperatively and 3, 6, 9, and 12 months postoperatively. RESULTS: The postoperative BCVA in the FSL-PK group, and the FSL-DALKb subgroup were significantly better than that in the FSL-DALKa subgroup (P < 0.05), whereas no differences were found between the FSL-DALKb subgroup and the FSL-PK group (P > 0.05). There were no significant differences in the mean spherical equivalent (SE) and astigmatism between the FSL-DALK and the FSL-PK groups, nor between the subgroups of FSL-DALK during the follow-up period (P > 0.05). At the last follow-up, the mean endothelial cell loss in the FSL-DALK group (9.12 %) was significantly less than that in the FSL-PK group (20.79 %) (P < 0.001), while there was no difference between the FSL-DALKa (9.15 %) and the FSL-DALKb (9.10 %) subgroups (P = 0.15). The FSL-DALK group seemed to have fewer graft rejections (1/28 cases) than the FSL-PK group (2/12 cases), although Kaplan-Meier curve showed no significant difference between the two groups (P = 0.144). CONCLUSIONS: In this retrospective study, the results suggested that FSL-DALKb gives better visual outcome, and FSL-DALKb is a better option for keratoconus whose endothelium is not compromised. However, larger and prospective studies are further required.